Current state of oak stands in eastern Polissya zone - Tkach, V. P.; Rumіantsev, M. Н.; Kobets, O. V.; Luk’yanets, V. A. (Forestry and Forest Melioration, 2019)
Introduction Oak stands (Quercus robur L.) are less common in the Eastern Polissya zone compared to Scots pine (Pinus sylvestris L.) and silver birch stands (Betula pendula Roth.). However, they are performing multifaceted ecological, protective, recreational and health improving functions. Moreover, oak stands provide the national economy with fine wood on account of final felling operations. At that, sustainable forest management is impossible to run without a thorough analysis of their current state. The aim of the study was to generalize forest mensuration indicators of the oak stands in the Eastern Polissya zone. Materials and Methods The ‘Ukrderzhlisproekt’ Production Association database was used to do the calculations. The results of the study were processed by means of the methods of the comparative analysis according to the generally accepted forestry approaches. The research covered forest fund of the 15 state forest enterprises (appr. 125 thousand subcompartments). Results Oak stands cover an area of 41,000 hectares which is 10% of the total area of the sites covered with forest vegetation. The oak forests within Eastern Polissya involve planted oak stands that cover 17,300 hectares (42% of the total area) and those of natural origin covering 23,800 hectares (58% of the total area). Their total stock volumes make 3.3 and 6.5 million m3 respectively. The stands of natural seed origin cover 15,700 hectares, while those of natural vegetative origin occupy 8,000 hectares. Furthermore, the exploitable oak stands prevail by their area (58%).The stands with conservational, academic, historical and cultural purposes cover large area as well (27%). The share of the recreational stands is 8%, and protective forests cover 6% of the total area. In the study region mostly mixed oak stands are common in the fresh and moist soil conditions. The associate and subsidiarytree species in the oak stands are European hornbeam (Carpinus betulus L.), Norway maple (Acer platanoides L.), small-leaved lime (Tilia cordata Mill.), aspen (Populus tremula L.), silver birch (Betula pendula Roth.), witch elm (Ulmus glabra Huds.), etc. The age structure of the oak stands is imbalanced with middle-aged stands prevailing. The area of the latter varies between 52% and 76%, depending on their origin. Furthermore, natural stands approaching maturity make a considerable part, namely 26% in the stands of vegetative origin and 29% in the stands of natural seed origin. Young stands make 22% in the sown oak stands. The oak stands with a relative density of stocking from 0.7 to 0.8 significantly prevail. They make 73% of the total area and include the I and II site classes regardless of their origin. Conclusions The conditions of the Eastern Polissya zone are favourable for valuable oak stands to grow. In the region, among the oak forests productive and stable oak stands of both planted seed origin and natural seed origin predominate. However, their age structure is imbalanced with middle-aged stands dominating. A considerable part of the stands includes approaching maturity, mature and overmature stands. The findings should be used when clarifying new maturity ages of the oak stands within the Eastern Polissya zone. At that, their origin, productive capacitys and forest category are to be taken into account. 3 Figs., 5 Tables, 30 Refs.